Study of Interfaces in Hf/Fe System Using Magneto‐Optical Kerr Effect and Soft X‐Ray Absorption Spectroscopy. Issue 11 (16th September 2020) - Vishwakarma, Pramod; Gupta, Mukul; Reddy, Varimalla R.; Phase, Deodatta M.; Gupta, Ajay
Abstract : Interface between layers of Fe and Hf is studied using magneto‐optical Kerr effect (MOKE) and soft X‐ray absorption spectroscopy (SXAS). Measurements as a function of the Fe layer thickness are done in a single sample by making use of a wedge‐shaped geometry for Fe layer sandwiched between two layers of Hf. SXAS measurements at the L‐edge of Fe provide evidence for interfacial alloying between Fe and Hf layers, with the thicknesses of the intermixed layers at Fe‐on‐Hf and Hf‐on‐Fe interfaces being 0.18 ± 0.05 and 0.27 ± 0.05 nm, respectively. Evolution of the MOKE hysteresis loop with Fe layer thickness gives an effective magnetic dead layer of 0.8 ± 0.1 nm at the two Fe/Hf interfaces together. Precise determination of the thickness of the intermixed layer and the magnetic dead layer using two independent techniques allows us to have a better insight into the interfacial magnetism and origin of magnetic dead layer at Fe/Hf interfaces. Present results suggest that the origin of the effective magnetic dead layer is partly due to modified magnetic moments of Fe and Hf in the intermixed regions and partly due to proximity‐induced magnetic moment in the interfacial Hf layers with its magnetic moment aligned antiparallel to the Fe layer. Abstract : Interfacial magnetism in Hf/Fe/Hf trilayer is studied using soft X‐ray absorption spectroscopy (SXAS) and magneto‐optical Kerr effect (MOKE). Precise determination of the thicknesses of intermixed layer and magnetic dead layer using two independent techniques provides a better insight into the interfacial magnetism; the interfacial magnetic dead layer is attributed partly to interfacial alloying and partly to proximity‐induced magnetism in Hf.